Sensitivity to temporal fine structure and hearing-aid outcomes in older adults - Perez Vallejos, Elvira; Mccormack, Abby; Edmonds, Barrie (Frontiers in Neuroscience, 2014)
Objective: to investigate the effect of sensitivity to temporal fine structure on subjective measures of hearing aid outcome. Design: Prior to receiving hearing aids, participants completed a test to assess sensitivity to temporal fine structure (TFS), the Glasgow Hearing Aid Benefit Profile (GHABP), and the Speech, Spatial and Qualities of hearing (SSQ-A). Follow-up appointments, comprised the GHABP, the SSQ-B , and the International Outcome Inventory for Hearing Aid Outcomes (IOI-HA). Study sample: 75 adults were recruited from direct referral clinics. Results: Two thirds of participants were found to have good sensitivity to TFS; listeners with good sensitivity to TFS rated their hearing abilities higher at pre-fitting (SSQ-A) than those with poor sensitivity to TFS. At follow-up, participants with good sensitivity to TFS showed a small improvement on SSQ-B over listeners with poor sensitivity to TFS. Conclusions: The clinical identification of a patient’s ability to process TFS information at an early stage in the treatment pathway could prove useful in managing expectations about hearing aid outcomes.